Improving Training Technologies for Beginner Tennis Players In the Initial Preparation Stage - Auezov, Islambek (Indonesian Journal Publisher, 2025)
This study examines the effectiveness of modern training technologies in improving the preparation of beginner tennis players during the initial development stage. Tennis is a highly complex coordination sport that requires synchronized technical execution, perceptual anticipation, physical readiness, and psychological stability. Traditional approaches focused mainly on repetitive drilling and isolated stroke practice prove insufficient for meeting the evolving demands of contemporary athlete development. This research therefore adopts a comprehensive theoretical–analytical methodology to explore technologically enhanced training methods, including progressive equipment modification, video analysis tools, wearable motion sensors, perceptual-cognitive training systems, footwork technologies, and gamified learning environments. Findings reveal that low-compression balls, scaled courts, and simplified racket designs significantly facilitate early acquisition of biomechanically correct stroke mechanics. Visual feedback technology accelerates error detection, strengthens internal movement representations, and improves technique retention. Perceptual-cognitive systems enhance anticipation, decision-making speed, and reaction timing, while footwork technologies promote kinetic chain efficiency and movement economy. Gamification and motivational tools increase engagement and emotional resilience, improving long-term adherence to the sport. Conditioning technologies support functional strength, coordination, and injury prevention. The results underscore that modernizing beginner tennis instruction requires integrating technological literacy with pedagogical expertise. The study concludes that technologically informed training models offer superior effectiveness, sustainability, and developmental advantages for novice players. Such innovations form the foundation for long-term athlete development, preventing early technical errors, enhancing motivation, and enabling smoother progression into advanced stages of tennis performance.